Pemenuhan Self Assessment System Dalam Pemungutan Bea Perolehan Hak Atas Tanah dan atau Bangunan Terhadap Jual Beli Tanah dan atau Bangunan di Kota Makassar - Alam, Azis; Dwi Nugroho, Adrianto (Recital Review, 2023)
The background of this research is the BPHTB collection system carried out by the Makassar City Regional Office for taxpayers including conducting comparisons of previous BPHTB prices, interviews with new taxpayers, comparisons with advertising prices for housing and making minutes of BPHTB tax determination resulting in the role of the taxpayer being passive. results in violating the self-assessment system. This research focuses on fulfilling the self-assessment system in collecting BPHTB. However, in reality this system has not been fully implemented due to dishonest taxpayers in notifying the actual transaction price. The purpose of this research is to find out and examine the effectiveness and implementation of the fulfillment of the self-assessment system in the BPHTB collection for buying and selling land and or buildings in Makassar City. The results of this study conclude first, the effectiveness of fulfilling the self-assessment system in collecting BPHTB for the sale and purchase of land and or buildings in Makassar City is seen based on the Makassar City BPHTB revenue data that the total target and realization of BPHTB taxes for the 2020 to 2022 fiscal year has decreased in realization of revenue from the target set. Second, the implementation of the fulfillment of the self-assessment system in collecting BPHTB for the sale and purchase of land and or buildings in Makassar City has not been implemented because the tax officer (Fiskus) still intervenes in determining the transaction price for BPHTB payments from taxpayers.